Nghiên cứu chế tạo, cấu trúc và tính chất của vật liệu cao su nanocompozit trên cơ sở cao su thiên nhiên, cao su cloropren gia cường nanoclay - Hải, Lương Như; Nguyên, Phạm Công; Tùng, Ngô Trịnh; Hùng, Lưu Đức; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2017)
Rubber nanocomposites based on NR/CR blends and nanoclays were prepared by rolling mill method. Nanoclays were treated by immersing in toluene before using. The effects of nanoclays contents on the mechanical, thermal properties of the materials were investigated. The morphology of the materials was characterized by X-Ray and transmission electron microscopy (TEM). The results reveal that the optimal nanoclays content for rubber nanocomposite was 5 %. The intercalated and exfoliated morphology of rubber nanocomposites were found. The reinforcements of nanoclay have significantly improved the tensile properties, thermal stability and environmental resistance of NR/CR blends. Keywords. NR/CR blend, nanoclay, nanocomposites